PENGEMBANGAN SISTEM INFORMASI PERPUSTAKAAN BERBASIS KARYA LOKAL UNTUK PENINGKATAN LITERASI KOMUNITAS (KBP) - Muhammad Tahir; Bukran Bukran; Muhammad Dava Aufa Emil Dava (UNIVERSITAS STEKOM, 2025)
This study aims to develop and implement a web-based Library Information System as a means to enhance literacy within the Kampoeng Baca Pelangi (KBP) Community. The system is designed to simplify library data management processes that were previously performed manually, including book cataloging, member registration, borrowing, returning, and the generation of operational reports. The development process follows the Waterfall method, starting from requirement analysis, system design, implementation, up to system testing. The results indicate that the system successfully meets the primary needs of the library administrators, based on feasibility testing involving internal KBP respondents. Evaluation through a Likert-scale questionnaire produced a score of 94%, indicating that the system falls into the “Highly Feasible” category for use. Features such as book data management, borrowing/return transaction processing, collection search, and report generation are proven to enhance the efficiency and accuracy of library operations.